Implementasi Peraturan Menteri Kesehatan Nomor 24 Tahun 2022 Tentang Rekam Medis Elektronik di Rumah Sakit X : mplementation of Minister of Health Regulation Number 24 of 2022 concerning Electronic Medical Records at Hospital X - Gea, Novi Kristanti; Hardiana, Hedy; Susanti, Fitria Aryani (Journal of Public Health Education, 2025)
Introduction: The Fourth Industrial Revolution has driven technological and service innovations that generate disruptive impacts and fundamental changes in various aspects of societal life in Indonesia. As part of the national digital health transformation strategy, the Ministry of Health has launched the Indonesia Health Services (IHS) platform to support the integration of health data and service applications. One key manifestation of this transformation is the implementation of Electronic Medical Records (EMRs), which contribute to improved documentation accuracy, reduced clinical errors, and faster access to patient information. Objectives: This study aims to evaluate the implementation of Electronic Medical Records (EMRs) at Hospital X in accordance with the Regulation of the Minister of Health of the Republic of Indonesia Number 24 of 2022 concerning the Organization of Medical Records. Methods: This study employed a qualitative approach, with data collected through in-depth interviews and direct observations of the EMR implementation process. Results: Hospital X has implemented EMRs using the Ekaliptus system provided by a third-party vendor. The implementation has generally complied with the established regulations, particularly in terms of leadership support, access authorization, and operational procedures, and has begun to foster a digital work culture. However, several challenges remain, including limited availability of supporting devices, suboptimal data entry compliance, and insufficient training and quality assurance supervision. Conclusion: Overall, the implementation of EMRs at Hospital X has had a positive impact on service efficiency. Nevertheless, challenges persist related to system integration, human resource training, facility availability, and the strengthening of governance mechanisms to achieve comprehensive digital integration.